Resistant starch's effect on blood glucose levels in individuals with prediabetes and diabetes mellitus: A systematic review - Fitri, Nurul; Yazid, Syahrul Abdul; Efendi, Cahyaningsih; Dewi, Yulis Setiya (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background: Diabetes ranks among the ten leading causes of mortality. Patients with diabetes who do not effectively manage their condition run the risk of developing severe complications. An appropriate dietary regimen is considered a fundamental aspect of effectively managing diabetes. One potential treatment option for diabetics is resistant starch (RS), which is supposed to control blood glucose levels. Objectives: The objective of this study is to investigate the impact of resistant starch on food items characterized by a high glycemic index.Methods: The methodology employed in this scholarly article is a systematic review. A comprehensive search was conducted across five prominent academic databases, namely EBSCO, PubMed, ProQuest, Scopus, and Google Scholar. The search strategy involved utilizing specific keywords, The presentation of the findings in this article adheres to the established guidelines and principles outlined in the Preferred Reporting Items for Systematic Review (PRISMA). Results: A total of eight statistically significant findings were observed, indicating that the consumption of starches effectively reduced blood sugar levels. The papers utilized genuine experimentation and quasi-experiment approaches within the past five years. Numerous interventions involving resistant starch have demonstrated efficacy in the reduction of blood glucose levels. These interventions include the retrogradation of rice, the consumption of natural starch found in bananas and whole grains, as well as the addition of oil during the cooking process of rice. Conclusions: The inclusion of different forms of resistant starch in the dietary regimen of individuals with diabetes may be a viable option. However, it is important to acknowledge the significance of incorporating complementary food items in addition to the primary staple foods that are consumed. The utilization of resistant starch has been found to be an effective strategy for reducing blood glucose levels among individuals with diabetes.